1988
DOI: 10.1002/nur.4770110204
|View full text |Cite
|
Sign up to set email alerts
|

Further exploration of maternal and paternal fetal attachment

Abstract: Fetal attachment of four groups of expectant parents were studied during the 24th to 34th weeks of pregnancy: 153 high-risk women hospitalized for a complication, 75 high-risk women's mates, 218 low-risk women, and 147 low-risk women's mates. No differences in fetal attachment scores were observed between high- or low-risk women or their mates; women scored significantly higher than their mates. Very little variance (7% to 14%) in fetal attachment was explained by the test of causal models except for high-risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
97
2
7

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 30 publications
14
97
2
7
Order By: Relevance
“…The challenge of developing interventions to promote positive appraisal coping strategies for women with complicated pregnancies lies in the sensitive balance between the realistic medical risk in the pregnancy and challenging negative hopeless appraisals that might inhibit attachment behaviours to the unborn baby. While the withholding of emotional commitment to the foetus may be a protective mechanism where the future of the infant is uncertain (Mercer et al, 1988), the current results suggest that medically assessed risk scores are unrelated to maternal appraisals of risk and unrelated to attachment scores. Hence, a woman who is perceived by her health professional to be at relatively low risk may still appraise herself and her baby to be at higher risk with potential negative influence on the development of attachment.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…The challenge of developing interventions to promote positive appraisal coping strategies for women with complicated pregnancies lies in the sensitive balance between the realistic medical risk in the pregnancy and challenging negative hopeless appraisals that might inhibit attachment behaviours to the unborn baby. While the withholding of emotional commitment to the foetus may be a protective mechanism where the future of the infant is uncertain (Mercer et al, 1988), the current results suggest that medically assessed risk scores are unrelated to maternal appraisals of risk and unrelated to attachment scores. Hence, a woman who is perceived by her health professional to be at relatively low risk may still appraise herself and her baby to be at higher risk with potential negative influence on the development of attachment.…”
Section: Discussionmentioning
confidence: 54%
“…Social support was investigated but was eliminated from the analysis at an early stage, as it was not related to either subscale of attachment. Existing literature pertaining to social support is contradictory: Mercer et al (1988) found no relationship between received social support and attachment for high-risk pregnant women and their partners; while Condon and Corkindale (1997) concluded that a lack of social support was detrimental to the development of maternal antenatal attachment in normal pregnancies. The current results do little to clarify the situation, possibly due (at least in part) to the low variability in satisfaction with social support (mean55.49, SD51.09) in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations